Hidrops Fetalis: Etiologi dan Tata Laksana - Angga Dominius (PT Kalbe Farma Tbk., 2024)
Hydrops fetalis (HF) is an abnormal fluid collection in two or more fetal compartments. HF is categorized as immune HF (IHF) and non-immune HF (NIHF). IHF is due to rhesus (Rh) incompatibility and NIHF is due to various pathologies. Management is according to underlying etiologies. Prognosis is determined by early diagnosis with ultrasonography (USG), medical intervention, and appropriate delivery time.